PENINGKATAN KEMAMPUAN BERPIKIR KRITIS, KEMANDIRIAN BELAJAR PKn SISWA MELALUI PROBLEM BASED LEARNING - rahimah ainun harahap (JURNAL TEMATIK, 2017)
The problem in this research is the teacher-centered learning that causes ability of low students’thinking. The purpose of this research is to know improvement of critical thinking ability, the learning independence of students  using PBL. The type of research is quasi experiment with the population  all of students SDN 067240 Medan Tembung and the sample in this study are the fourth grade students by taking two classes (experimental class and class control) of 50 students. The instrument used consists  of critical thinking skills and learning independence scales. Data are  analyzed by using  two-way ANAVA test. Based on the results of the analysis are obtained: (1) The improvement of critical thinking skills of students who are given problem-based learning is higher than students who are given conventional learning; (2) There is no interaction between learning with students 'early math ability to improve students' critical thinking ability; (3) The  increasing of the students in learning  independence  given problem based learning is higher than students who are given conventional learning. Based on the results of this study, it is suggested that problem based learning can  be used as an alternative for teachers to improve the ability of critical thinking  of students and learning independence of students.